Elaborations on L2 interactional competence: the development of L2 grammar-for-interaction. Issue 1 (2nd January 2018) - Pekarek Doehler, Simona
Abstract: This paper argues for a broadening of the analytic scope of research on L2 interactional competence so as to embrace systematic investigation of the linguistic resources that L2 speakers put to use for the specific purpose of coordinating social interaction. The paper first offers a conceptualisation of interactional competence in terms of systematic procedures (or: methods) for action that is firmly grounded in Ethnomethodology and Conversation Analysis. Drawing on interactional linguistics, the paper then discusses an understanding of grammar as an adaptive and emergent set of resources by means of which participants accomplish actions in mutually recognisable ways, and suggests that this understanding can fruitfully be brought to bear on L2 development. In the main body of the paper, evidence is provided for the development of an L2 grammar-for-interaction regarding three distinct grammatical constructions, and an initial sketch of a developmental trajectory is proposed. Based on the findings, the paper argues that a fuller understanding of L2 interactional competence requires systematic investigation of the entire multisemiotic toolbox, including linguistic and embodied resources that participants draw on for meaning-making in social interaction. It concludes with implications for understanding the affordances of classroom interaction and with avenues for future research.